L-Convex Sublattice of an L-Lattice and Complement of an L-Set (European Journal of Pure and Applied Mathematics, 2025)
In this paper, the authors define and explore the notion of an L-convex sublattice in an L-lattice. The investigations in this paper lead to ’The Unique Representation Theorem’ for L-convex sublattices. Also, the authors effectively use the concept of  order reversing involution on the lattice L of truth values to define complement of an L-set. Further, they employ this notion in the studies of L- prime ideals and L-maximal ideals.
Keywords: Lattices; generated L-sublattice, generated L-ideal; generated L-dual ideal; L-convex sublattice; L-maximal ideal; L-prime ideal